Experimental Research with Computer Simulation (Case Study Of Urban Cool Island) - Yaseri Dahlia Apritasari; Iwan Sudrajat; Surjamanto Wonorahardjo (International Journal of Built Environment and Scientific Research, 2023)
This research will describe experimental research methodology using computer simulation with the case study of urban cool island research. The urban cool island is one of the urban heat island mitigation technology strategies. This technology uses a geometric and material intervention process that forms an urban cool island in an area with high urban heat island intensity. The urban cool island will expand and reduce the temperature of the hot islands so that the urban heat island gets smaller. In the research process, a series of experimental methodologies were carried out. Experimental methodology is carried out on a regional scale will be difficult and expensive. So a computer simulation is needed to facilitate urban cool island experiments in the area. The stages of experimental research with computer simulations use two process stages (1) Quasi-measurement experiments and field observations in the UCI area, (2) Validation of field measurements versus simulation models, (3) Experiments with computer simulations by creating test models and comparison models. The scope of research on the scale of urban areas with experimental methodology becomes efficient with the help of computer simulations. In Urban Cool Island, several countries have also used this methodology. Computer simulation used: ENVI-MET, CFD-Ansys, and others. Before starting the research, a clear frame or research design is needed, determining variables, replicating the real conditions, mastering the use of simulations, and always paying attention to the results, which are continuously controlled and validated to produce simulations that are close to the real conditions.